A conceptual framework for cross-border impacts of climate change. (July 2021) - Carter, Timothy R.; Benzie, Magnus; Campiglio, Emanuele; Carlsen, Henrik; Fronzek, Stefan; Hildén, Mikael; Reyer, Christopher P.O.; West, Chris
Graphical abstract: Highlights: We define cross-border climate impacts and identify challenges they may pose. We develop a conceptual framework to help understand them and their dynamics. The framework can organise and offer useful insights into past and projected cases. To demonstrate we use examples of the 2011 Thai floods and Arctic sea ice decline. The complexity of impact dynamics suggests a need for diverse adaptation responses. Abstract: Climate change impacts, adaptation and vulnerability studies tend to confine their attention to impacts and responses within the same geographical region. However, this approach ignores cross-border climate change impacts that occur remotely from the location of their initial impact and that may severely disrupt societies and livelihoods. We propose a conceptual framework and accompanying nomenclature for describing and analysing such cross-border impacts. The conceptual framework distinguishes an initial impact that is caused by a climate trigger within a specific region. Downstream consequences of that impact propagate through an impact transmission system while adaptation responses to deal with the impact propagate through a response transmission system. A key to understanding cross-border impacts and responses is a recognition of different types of climate triggers, categories of cross-border impacts, the scales and dynamics of impact transmission, the targets and dynamics of responses and the socio-economic and environmental context that also encompasses factors and processes unrelated to climate change. These insights can then provide a basis for identifying relevant causal relationships. We apply the framework to the floods that affected industrial production in Thailand in 2011, and to projected Arctic sea ice decline, and demonstrate that the framework can usefully capture the complex system dynamics of cross-border climate impacts. It also provides a useful mechanism to identify and understand adaptation strategies and their potential consequences in the wider context of resilience planning. The cross-border dimensions of climate impacts could become increasingly important as climate changes intensify. We conclude that our framework will allow for these to be properly accounted for, help to identify new areas of empirical and model-based research and thereby support climate risk management.